IMPACT OF ASSESSMENT TO AN ULTRASONIC AND SOME OF IMMUNE-HISTOCHEMICAL PARAMETERS OF A COMBINED TWO-STAGE TREATMENT OF CHRONIC ENDOMETRITIS OF INFERTILE PATIENTS WITH THE PROLONGED COURSE OF AMPLIPULSETHERAPY - Скоропацкая, Ольга Алексеевна; Яворская, Светлана Дмитриевна; Фадеева, Наталья Ильинична (Mother and Baby in Kuzbass, 2018)
The aim of of research – determine the effectiveness of two-stage therapy of chronic endometrium through the use of recuperating a three-month course of amplipulsetherapy Materials and methods. Monocentropus conducted, a prospective study in a group of patients (n = 25) with chronic endometritis and infertility that are at the stage of rehabilitation received a prolonged course of amplipulsetherapy. The course of amplipulsetherapy consisted of 10 daily treatments with 5-7 at the 17-20 day cycle with a break on weekends, the unit «Amplipuls-5». Pipel biopsy of the endometrium was performed on the 5-7 day of the cycle with subsequent histological and histochemical studies of the biopsy. Immunohistochemical determination of the nature of inflammation was carried out according to the method of E.A. Mignini. Statistical analysis of the results was carried out using the program for static processing of Statistical 10. Results. Upon completion of therapy, all patients showed an improvement in the histological picture in the form of a decrease in the frequency of lymphocytic infiltration, represented only by a diffuse form (100 % and 20 %; p = 0.00001). Conclusion. We have developed a two-step technique of therapy chronic endometritis, with the use of prolonged amplipulsetherapy on the stage of rehabilitation allows to achieve a significant improvement of the endometrium according to the ultrasound, restoration of normal structure according to PayPal hysteroscopy and biopsy in 70 % of cases.